2019
DOI: 10.3389/fmicb.2019.01464
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing-Based Comparison of Food Isolates of Cronobacter sakazakii

Abstract: Cronobacter sakazakii is an emerging foodborne pathogen, which is linked to life-threatening infections causing septicemia, meningitis, and necrotizing enterocolitis. These infections have been epidemiologically connected to ingestion of contaminated reconstituted powder infant formula. Even at low water activity C. sakazakii can survive for a long time; it is capable of protective biofilm formation and occasionally shows high virulence and pathogenicity even following stressf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 133 publications
1
26
0
Order By: Relevance
“…The antibiotic target protection gene (vgaC) was present in only three of the six isolates and the marA gene, whose function is as a transcription factor that upregulates multidrug efflux and downregulates membrane permeability, was found in all the isolates. As in our study, Aly et al [69] found msbA, emrR, H-NS, emrB, marA, CRP, and PBP3 to be associated with resistance to several antibiotics such as beta-lactams, tetracycline, macrolide, fluoroquinolone, penams, cephalosporin, and cephamycin. Active flow pumps provide a mechanism to increase resistance by improving the survival of enterobacteria in the gastrointestinal tract of the host and allowing the invasion of microvascular endothelial cells in the brain [70,71].…”
Section: Resultssupporting
confidence: 86%
“…The antibiotic target protection gene (vgaC) was present in only three of the six isolates and the marA gene, whose function is as a transcription factor that upregulates multidrug efflux and downregulates membrane permeability, was found in all the isolates. As in our study, Aly et al [69] found msbA, emrR, H-NS, emrB, marA, CRP, and PBP3 to be associated with resistance to several antibiotics such as beta-lactams, tetracycline, macrolide, fluoroquinolone, penams, cephalosporin, and cephamycin. Active flow pumps provide a mechanism to increase resistance by improving the survival of enterobacteria in the gastrointestinal tract of the host and allowing the invasion of microvascular endothelial cells in the brain [70,71].…”
Section: Resultssupporting
confidence: 86%
“…We observed similar communities and reported the presence of pathogens, that could infect humans and animals, associated with rotting grapes, such as C. sakazakii SRG2, K. pneumoniae SRG3, and S. gigas SRG18. C. sakazakii is an emerging opportunistic foodborne pathogen with the potential to cause meningitis, bacteremia, and necrotizing enterocolitis, particularly in infants (Drudy et al, 2006;Aly et al, 2019). K. pneumoniae is an important conditional pathogenic and iatrogenic infectious bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the whole genome sequencing (WGS)-based approach from cultured bacterial isolates has emerged as one of the most comprehensive tools for surveillance study, drug resistance determination, and evolutionary analysis of infectious diseases [219,220,221,222,223,224]. This is due to improved sequencing technologies, the user friendly nature, easy availability of reagents, improved accuracy of up to 93%, reasonably lower costs (150EUR per 5 MB genome by Illumina MiSeq), and faster results (nine days versus 21 days) compared to traditional DNA sequencing [221,222,225,226,227].…”
Section: Whole Genome Sequencing and Genome Wide Association Studimentioning
confidence: 99%
“…Similarly, another study was conducted by Edwards et al to characterize the putative virulence factors in Plesiomonas shigelloides [228]. Furthermore, Aly et al used a WGS-based study to identify genes associated with biofilm formation, antibiotic resistance, and pathogenicity [224]. The results of these studies clearly suggest that WGS-based approaches are an advancement over traditional Sanger sequencing.…”
Section: Whole Genome Sequencing and Genome Wide Association Studimentioning
confidence: 99%